Raising awareness of prisoners about restorative justice and victims: An example of the program implemented in the women’s prison in Serbia - Ćopić Sanja; Nikolić-Ristanović Vesna (Temida)
Restorative justice is implemented in a variety of fields, contexts and situations. One possible way of implementing restorative justice is seen in introducing restorative approaches into the prison settings. It is argued that restorative justice can add more humanity into the prison system; it may help in treatment of prisoners and contribute to their preparation for the release and easier reintegration and social inclusion. Introducing victims’ perspective, either through their direct involvement in restorative justice programs in prisons or through working on raising awareness of inmates about victims and their rights, needs and feelings, contributes to increase of the visibility of victims, their empowerment and healing. Taking that as a starting point, the article aims at presenting one possible way of introducing restorative justice into the prison setting through raising awareness programs for prisoners about restorative justice and victims’ rights, which are implemented in some European and non-European countries. It particularly focuses on presenting the program on raising awareness about the impact of crime on a victim and on restorative justice, which was developed by the Victimology Society of Serbia as a part of its long-term advocacy and support to female prisoners. This is an integrated, gender-sensitive program developed in the spirit of positive criminology and victimology. It was piloted in 2015 in the women’s prison in Serbia. The program was implemented in a form of a series of six workshops followed by evaluation interviews with female prisoners who took part in the entire program. The program evaluation suggested that participants improved their overall knowledge related to victims; they also showed the desire to apologize to person(s) they had hurt and they recognized that the program had influenced them to change in a positive way, especially in terms of diverting from hurting others by a crime or other harmful acts. Participants also recognized the potential of restorative mechanisms in their relationship with their own victims, but also with other people. Evaluation showed that participants used learnt skills after the program ended, particularly communication skills in the spirit of restorative justice, focusing on the present moment and yoga nidra. Development and delivery of the victim awareness raising program piloted in the women’s prison in Serbia proved to be valuable learning experience. Keeping in mind lessons learnt, it is obvious that there is a need for broader use of restorative justice approaches in prison settings for both adults and juveniles in Serbia. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 179044: Metodologija evidentiranja kriminaliteta kao osnova efikasnih mera za njegovo suzbijanje i prevenciju]